Proceedings of the 1st Unimed International Conference on Sport Science (UnICoSS 2019) 2020
DOI: 10.2991/ahsr.k.200305.010
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of e-Learning Toward Student Learning Outcomes

Abstract: This study seeks to determine the impact of elearning in education on students' learning outcome. We employ a quasi-experimental design in this study. The subject of this study consisted of students of Sport Science Faculty at State University of Medan. The independent variables in this study are e-learning using an Edmodo platform that serves to provide elearning materials and conventional learning method. The dependent variable is the students' learning outcome. The data of learning outcomes were analyzed us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…At the level of quantitative results, using PLS-SEM Islam (2013) confirmed that e-Learning adoption antecedents (ease of use, utility, enjoyment, system quality, information quality, service quality, self-efficacy, usability, and playfulness) have an impact on e-Learning adoption outcomes (learning assistance, community building assistance, and academic performance). Goh et al (2017) confirmed that e-Learning courses maximize student learning outcomes in Malaysian universities; Ritonga et al (2020) also concluded that e-Learning has an impact on student learning outcomes. Baber (2020) confirmed that the factors-interaction in the classroom, course structure, instructor knowledge, and facilitation in e-Learning systems are positively influencing students' perceived learning outcomes.…”
Section: Discussionmentioning
confidence: 72%
“…At the level of quantitative results, using PLS-SEM Islam (2013) confirmed that e-Learning adoption antecedents (ease of use, utility, enjoyment, system quality, information quality, service quality, self-efficacy, usability, and playfulness) have an impact on e-Learning adoption outcomes (learning assistance, community building assistance, and academic performance). Goh et al (2017) confirmed that e-Learning courses maximize student learning outcomes in Malaysian universities; Ritonga et al (2020) also concluded that e-Learning has an impact on student learning outcomes. Baber (2020) confirmed that the factors-interaction in the classroom, course structure, instructor knowledge, and facilitation in e-Learning systems are positively influencing students' perceived learning outcomes.…”
Section: Discussionmentioning
confidence: 72%
“…Through electronic-based learning resources, various benefits can also be obtained, such as more flexibility in time and place for students to utilize these learning resources (Abed, 2019;Sagita & Khairunnisa, 2020). In addition, the use of electronic learning resources can also optimize students' learning outcomes (Ritonga et al, 2020;Sidauruk et al, 2021) and other competencies (Haghparast et al, 2014;Zare et al, 2016). The form of learning resources also needs to be chosen appropriately in order to be able to facilitate students to become independent learners.…”
Section: Introductionmentioning
confidence: 99%
“…E-learning supports studentcentered learning because students no longer depend on lecturers. After all, lecturers are one of many sources of knowledge for students (Ritonga et al 2019).…”
Section: Introductionmentioning
confidence: 99%